1999
DOI: 10.1073/pnas.96.15.8522
|View full text |Cite
|
Sign up to set email alerts
|

Hsl7p, a negative regulator of Ste20p protein kinase in the Saccharomyces cerevisiae filamentous growth-signaling pathway

Abstract: In the budding yeast, Saccharomyces cerevisiae, protein kinases Ste20p (p21 Cdc42p͞Rac -activated kinase), Ste11p [mitogen-activated protein kinase (MAPK) kinase kinase], Ste7p (MAPK kinase), Fus3p, and Kss1p (MAPKs) are utilized for haploid mating, invasive growth, and diploid filamentous growth. Members of the highly conserved Ste20p͞ p65 PAK protein kinase family regulate MAPK signal transduction pathways from yeast to man. We describe here a potent negative regulator of Ste20p in the yeast filamentous grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 43 publications
4
36
0
Order By: Relevance
“…The most frequently isolated two-hybrid clone was skb1 1 , which encodes an arginine methyltransferase, an ortholog of S. cerevisiae Hsl7 (Fujita et al 1999;Shulewitz et al 1999;Lee et al 2000). We observed no obvious genetic interactions between Dskb1 and mst1-L344S, in contrast to budding yeast where hsl7 and esa1 mutants have been shown to have synthetic interactions (Ruault and Pillus 2006).…”
Section: Resultsmentioning
confidence: 58%
“…The most frequently isolated two-hybrid clone was skb1 1 , which encodes an arginine methyltransferase, an ortholog of S. cerevisiae Hsl7 (Fujita et al 1999;Shulewitz et al 1999;Lee et al 2000). We observed no obvious genetic interactions between Dskb1 and mst1-L344S, in contrast to budding yeast where hsl7 and esa1 mutants have been shown to have synthetic interactions (Ruault and Pillus 2006).…”
Section: Resultsmentioning
confidence: 58%
“…Overexpression of the G " cyclins CLN1 and CLN2 enhances filamentous and invasive growth, represses pheromone signalling, and results in phosphorylation of Ste20 (Fujita et al, 1999 ;Madhani et al, 1999 ;Oehlen & Cross, 1998). However, another study demonstrated that Cln1 and Cln2 act in parallel to the STE MAPK pathway during filamentous growth (Loeb et al, 1999).…”
Section: Mapk-stimulated Filamentous Growthmentioning
confidence: 99%
“…However, another study demonstrated that Cln1 and Cln2 act in parallel to the STE MAPK pathway during filamentous growth (Loeb et al, 1999). Hsl7, a negative regulator of the Swe1 protein kinase, apparently also binds to Ste20 and Cdc42 (Fujita et al, 1999). HSL7 deletion induces cell elongation and filament formation in rich medium, but this phenotype is diminished by a STE20 deletion.…”
Section: Mapk-stimulated Filamentous Growthmentioning
confidence: 99%
“…The methyltransferase Hsl7 negatively regulates Ste20 function in this pathway. Hsl7 binds to the N-terminal region of Ste20, possibly competing with Cdc42 (Fujita et al, 1999). Interestingly, Skb1, a fission yeast homolog of Hsl7, has been shown to have the opposite effect: it positively modulates Pak1 function and binds to a site on Pak1 that is different from that which binds Cdc42 (Gilbreth et al, 1996).…”
Section: Paks and Mapksmentioning
confidence: 99%